PARTISIPASI KELOMPOK SADAR WISATA DALAM PENGEMBANGAN PARIWISATA HALAL DI DESA SESAOT KECAMATAN NARMADA KABUPATEN LOMBOK BARAT - Hermanto Hermanto; Siti Nurmayanti; Muhammad Ma'ruf; Noni Antika Khairunnisah; Lalu Gde muhamad Subhan; Vina Ayu Hidayati; Lalu Ferdi Ferdiansyah (Master of Management, Mataram University, 2020)
This research is qualitative and quantitave research of Considered Tourist Group Participation of Halal Tourism Development at Sesaot Village, Narmada, West Nusa Tenggara. The result of research shows that the Tourist Group Participation is enthusiast, seen from the initiative of Tourist Group, destination managerial, empowerment and community participation. There two factors in this research such as supporting and inhibiting factors. The supporting factor is obtanied from outside they are natural resources, the role and support of the government and the involvement of Tourist Group which is the sustainable tourism observatory (STO), the driving force and support for Tourist Group to develop and exploit their tourism potential at Sesaot village. Currently, Sesaot tourism is already reached of utilizing the results. While, the inhibiting factors is the lack of understanding and knowledge of Tourist Group about tourism and the lack of funds.Keywords :Considered Tourist Group Participation, Halal Tourism Development, Sesaot Village.